2013
DOI: 10.1016/j.neunet.2012.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Prespeech motor learning in a neural network using reinforcement

Abstract: Vocal motor development in infancy provides a crucial foundation for language development. Some significant early accomplishments include learning to control the process of phonation (the production of sound at the larynx) and learning to produce the sounds of one’s language. Previous work has shown that social reinforcement shapes the kinds of vocalizations infants produce. We present a neural network model that provides an account of how vocal learning may be guided by reinforcement. The model consists of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…It might therefore serve as a guide for future work on more detailed models in order to include realistic social response rates and learning rates while at the same time including more specific neural and physiological bases for the child behaviors and for the learning mechanisms. For example, would existing neural network models of learning to produce speech sounds via reinforcement, such as [35] or [36], if given realistic numbers of trials and adult reinforcement rates, also yield good fits to human data? Relatedly, future extensions of this work both on the human side and on the modeling side should take into account more detailed information about the acoustics and semantics [38] of child and adult vocalizations.…”
Section: Discussionmentioning
confidence: 99%
“…It might therefore serve as a guide for future work on more detailed models in order to include realistic social response rates and learning rates while at the same time including more specific neural and physiological bases for the child behaviors and for the learning mechanisms. For example, would existing neural network models of learning to produce speech sounds via reinforcement, such as [35] or [36], if given realistic numbers of trials and adult reinforcement rates, also yield good fits to human data? Relatedly, future extensions of this work both on the human side and on the modeling side should take into account more detailed information about the acoustics and semantics [38] of child and adult vocalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Then a caregiver is used to produce speech by using speech sounds for object names using reinforcement learning, where the reward is again given by the response of the caregiver. Likewise, a selforganizing map together with reinforcement learning was proposed in Warlaumont (2013), which demonstrated that the reinforcement learning based on the similarity of vocalization can improve the post-learning production of the sound of one's language.…”
Section: Language Understanding For Robot Systemsmentioning
confidence: 99%
“…Motorskill learning is influenced by reward (e.g., Buitrago, Ringer, Schulz, Dichgans, & Luft, 2004; Izawa & Shadmehr, 2011), so it is plausible that contingent social responses positively reinforce children both with and without ASD as they develop motor speech skills. Supporting this possibility, several computational models have shown how speech learning can be viewed as a type of motor learning that is influenced by reward (Howard & Messum, 2014; Miura, Yoshikawa, & Asada, 2012; Warlaumont & Finnegan, 2016; Warlaumont, Westermann, Buder, & Oller, 2013). …”
Section: Motor Ability Communicative Motivation and The Social-feedmentioning
confidence: 99%